"Pincer" Pyridine–Dicarbene–Iridium and ‐Ruthenium Complexes and Derivatives Thereof. Issue 35 (9th September 2020) - Danopoulos, Andreas A.; Braunstein, Pierre; Saßmannshausen, Jörg; Pugh, David; Wright, Joseph A.
Abstract : The cationic pincer‐type complexes [Ir I (CN Me C)L]X {CN Me C = [2, 6‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene]‐3, 5‐dimethylpyridine, L = CO, X = PF6 4 ; L = CH3 CN, X = PF6 5 ; L = pyridine, X = BAr F 4, Ar F = 3, 5‐bis‐trifluoromethyl‐phenyl 6 }, that were obtained from [Ir I (CN Me C)Cl] (1 ) by displacement of the chloride ligand were structurally characterized. Complexes 4 and 5 adopt square planar, in‐plane distorted geometries, and in 6 the metal environment shows substantial pyramidalization. Theoretical calculations of the cations in 4 and 6 reproduce the experimental structures and rationalize their features. 1 undergoes oxidative transformations with CH2 Cl2 to cis ‐[Ir III (CN Me C)(CH2 Cl)Cl2 ] (7 ) and with PhICl2 to mer ‐[Ir III (CN Me C)Cl3 ] (8 ). The ruthenium derivatives trans ‐[Ru II (CNC)Cl2 L] {CNC = [2, 6‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene]‐pyridine, L = pyridine, 10 } and [Ru II (CNC)(η 2, η 2 ‐nbd)](X)2 . 2L (nbd = 2, 5‐norbornadiene, L = CH3 CN, X = BF4 11 ), were prepared by the reaction of cis‐trans ‐[RuCl2 (nbd)(py)2 ] and trans ‐ cis ‐[RuCl2 (nbd)(pip)2 ] (pip = piperidine) with the ligand CNC, respectively; both adopt distorted octahedral structures. The back‐bonding in 11 is comparable to that in its precursor complex, indicating minimal contribution of the NHC donors to this effect. Substitution of both chlorides in the known cis ‐[Ru II (CNC)Cl2 L] (L = PPh3 ) by azido ligands gave cis ‐[Ru II (CNC)(N3 )2 L] (L = PPh3, 12 ), which by photolytic cleavage of the coordinated N3 failed to produce well‐defined complexes. Abstract : Synthesis, reactivity, structures and bonding analyses of Ir I pincer‐type complexes are reported. Specific geometrical distortions away from regular square‐planar are discussed in the context of NCI. Analogous Ru II complexes are also presented.